About the nature of the background in the internal friction spectrum of polycrystalline palladium - A. A. Gorshkov; V. A. Lomovskoy; E. K. Naimi (Тонкие химические технологии)
Analysis of the dissipation phenomena in the polycrystalline palladium in the range of temperatures from 120K to 800 K was conducted based on the spectrum of internal friction. It has been determined that set of relaxation mechanisms and kinetic phenomena contribute to the background of the spectrum.